(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Water is the most essential component of all life on Earth. It accounts for around 71.4 percent of the earth’s surface. It is the most prevalent chemical in the human body. In a city of 20,000 inhabitants, the average daily water use is 200 litres. To fulfil the public’s enormous demand, water must be stored and supplied. The demand for water does not remain consistent throughout the day. It differs from one hour to the next. We must save water in order to provide a consistent volume of water. As a result, a water tank must be built to supply the public’s water needs. Water, liquid petroleum, petroleum products, and similar liquids are stored in storage reservoirs and overhead tanks. Regardless of the chemical composition of the substance, the force analysis of reservoirs or tanks is roughly the same. To prevent leaking, all tanks are built as crack-free constructions. Water is also essential in the agricultural and industrial sectors. Water demand is a critical problem in water supply planning. To address this issue, current water tank designs must be updated. The most effective storage facility utilised for home or even industrial purposes is an above water tank.